2019
DOI: 10.1002/ajp.23023
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic assessment of the Cebus apella gut microbiota

Abstract: Cebus Apella (C. apella) is a species of Nonhuman Primate (NHP) used for biomedical research because it is phylogenetically similar and shares anatomical commonalities with humans. Here, the gut microbiota of three C. apella were examined in the different regions of the intestinal tract. Using metagenomics, the gut microbiota associated with the luminal content and mucus layer for each intestinal region was identified, and functionality was investigated by quantifying the levels of short chain fatty acids (SCF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
1
5
2
Order By: Relevance
“…Notably, the important human gut bacterium, Akkermansia [34], was not detected in the baboon gut. Therefore, Akkermansia was more humanspecific and thus absent in the baboons in our study, no Akkermansia has been reported in NHPs [35,36].…”
Section: Discussioncontrasting
confidence: 55%
“…Notably, the important human gut bacterium, Akkermansia [34], was not detected in the baboon gut. Therefore, Akkermansia was more humanspecific and thus absent in the baboons in our study, no Akkermansia has been reported in NHPs [35,36].…”
Section: Discussioncontrasting
confidence: 55%
“…Notably, the important human gut bacterium, Akkermansia [37], was not detected in the baboon gut. Therefore, Akkermansia was more like human-specific and thus absent in the baboons in our study, no Akkermansia has been reported in NHPs [38,39].…”
Section: Discussioncontrasting
confidence: 51%
“…16S rRNA sequencing was performed and proportional analysis of bacterial community composition at the family genus level showed that, as in previous studies on the Cebus apella microbiome, Streptococcaceae Streptococcus and Lactobacillaceae Lactobacillus are dominant members of the gut microbial community (data not shown). 36 Overall, there were many fluctuations in the microbial community found in the fecal samples throughout the experiment, as such, there were not any statistically significant differences in proportional abundance before and after SN Stevia. However, at the genus level we did observe an increase in the Comamonas, Granulicatella, Sphingobacterium, and the Wautersiella genera (data not shown).…”
Section: Sn Stevia and Erythritol Increases Butyric Acid But Does Not...mentioning
confidence: 83%
“…The animal was chosen according to the same standards as Firrman et al 2019. 36 Following a 1 week control period, the animal was fed 62 mg/kg Splenda Naturals plus Stevia per day for 2 weeks. Fecal samples were collected and frozen immediately at −80 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation